Cover Image, Volume 30, Issue 6. (June 2017) - Jung, Won‐Beom; Han, Yong Hee; Chung, Julius Juhyun; Chae, Sun Young; Lee, Sung Hoon; Im, Geun Ho; Cha, JiHoon; Lee, Jung Hee
Abstract : The cover image, by Won‐Beom Jung et al., is based on the Research Article Spatiotemporal microstructural white matter changes in diffusion tensor imaging after transient focal ischemic stroke in rats, DOI:10.1002/nbm.3704 .